2008
DOI: 10.1248/cpb.56.1704
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Flowers. XXIV. Chemical Structures and Hepatoprotective Effects of Constituents from Flowers of Hedychium coronarium

Abstract: Hedychium coronarium KOEN. (Zingiberaceae) is widely cultivated in Japan, India, South China, and Southeast Asian countries. The rhizomes of H. coronarium have been used for the treatment of headache, contusion inflammation, and sharp pain due to rheumatism in Chinese traditional medicine. Previously, we reported that the extract from the rhizomes of H. coronarium showed inhibitory effects on increase in vascular permeability and nitric oxide production and on the release of b-hexosaminidase from RBL-2H3 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…As the chemical constituents from this herbal medicine, several a-pyrones, flavonoids, chalcones, and phthalides were isolated from the flowers 3,4) and roots. 5,6) During the course of our characterization studies on medicinal flowers, 1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] we found that the methanolic extract from the flowers of H. arenarium inhibited on tumor necrosis factor-a (TNF-a)-induced cytotoxicity in L929 cells. TNF-a is known to mediate a number of forms of organ injury through its induction of cellular apoptosis.…”
mentioning
confidence: 99%
“…As the chemical constituents from this herbal medicine, several a-pyrones, flavonoids, chalcones, and phthalides were isolated from the flowers 3,4) and roots. 5,6) During the course of our characterization studies on medicinal flowers, 1,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] we found that the methanolic extract from the flowers of H. arenarium inhibited on tumor necrosis factor-a (TNF-a)-induced cytotoxicity in L929 cells. TNF-a is known to mediate a number of forms of organ injury through its induction of cellular apoptosis.…”
mentioning
confidence: 99%
“…ex BAKER cultivated at Loei province, Thailand were purchased from a Thai traditional drug store in Nakhonsithammarat province, Thailand on Effects on D-GalN-Induced Cytotoxicity in Primary Cultured Mouse Hepatocytes The hepatoprotective effect of the constituents were determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay using primary cultured mouse hepatocytes. [48][49][50][51][53][54][55][56] Hepatocytes were isolated from male ddY mice (30-35 g) by collagenase perfusion method. A cell suspension at 4×10 4 cells in 100 μL William's E medium containing FCS (10%), penicillin G (100 units/mL), and streptomycin (100 μg/mL) was inoculated in a 96-well microplate and precultured for 4 h at 37°C under a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, 30,48-57) As a continuing exploratory study for hepatoprotective agents from medicinal plants, the constituents from the rhizomes of K. parviflora were examined. As shown in Table 4, 5,3′-dihydroxy-3,7,4'-trimethoxyflavone (14, IC 50 =18.4 μM) showed higher activity than silybin (38.8 μM), 49,50,[53][54][55][56] a commercial hepatoprotective agent as a positive control.…”
mentioning
confidence: 99%
“…Previous phytochemical investigation of H. coronarium has resulted in the identification of a number of labdane diterpenes, which were proved to be the main components. [7][8][9][10] Labdane diterpenes occur in several plants of the Zingiberaceae family and have been reported to possess anti-inflammatory properties. 11,12) Interestingly, our extensive phytochemical study of the rhizomes of H. coronarium led to the isolation of two new and four known labdane-type diterpenoids.…”
mentioning
confidence: 99%